2018
DOI: 10.4103/ejd.ejd_188_18
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and surface properties analysis of restorative materials submitted to erosive challenges in situ

Abstract: Objective:This study aims to evaluate the effect of acidic solutions (AS) on surface roughness (Ra) and microhardness of restorative materials (RM).Materials and Methods:Eight volunteers wore intraoral palatal devices (IPD) containing samples of RM: Ketac Nano (KN); Ketac Nano + Biscover LV (KN-B); Esthet-X (EX); Esthet-X + Biscover LV (EX-B); Supreme XT (SXT); Supreme XT + Biscover LV (SXT-B); and bovine enamel. The samples were submitted to three phases: (1) immersion in 0.01M hydrochloric acid (HCl) – 10 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
0
13
0
2
Order By: Relevance
“…19 The organic matrix, the filler particle and the polishing of the restorations can increase the physical properties making it more resistant to degradation. 37 Inadequate polymerization of adhesive resin-based restorations has been related to clinical failures due to a greater chance of fracture, secondary caries, and/or premature wear. 35,38,39 Overall, DoC is evaluated according to ISO 4049 standard, but comparing the ISO standard with hardness profile, it was found that there is an overestimation in relation to the DoC.…”
Section: Discussionmentioning
confidence: 99%
“…19 The organic matrix, the filler particle and the polishing of the restorations can increase the physical properties making it more resistant to degradation. 37 Inadequate polymerization of adhesive resin-based restorations has been related to clinical failures due to a greater chance of fracture, secondary caries, and/or premature wear. 35,38,39 Overall, DoC is evaluated according to ISO 4049 standard, but comparing the ISO standard with hardness profile, it was found that there is an overestimation in relation to the DoC.…”
Section: Discussionmentioning
confidence: 99%
“…While it would be tempting to relate the beginning of wear due to silane degradation, 13,14,21 resin composite surface wear is a multifactorial phenomenon and is usually material dependent and cannot be predicted from resin composite category, filler loading, and resin matrix. 22,23 Other effects of degradation may include reduction of fracture toughness, 24 flexure strength, 25,26 surface roughness, 27,28 all of which may cause early restoration failure.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the clinical insertion like ceramic laminates, the use of resin restorations is still very common because of its cost-effectiveness and its more conservative preparation. In the field of restorative dentistry, it has been proved that the action of acidic beverages on resin composites may cause changes in their microhardness due to the disruption of the interactions between the monomers present in their polymeric matrixes [4].…”
Section: Introductionmentioning
confidence: 99%